The Electrochemical and Surface Studies of the Corrosion Behavior of Sputter-deposited W-Ni Alloys in 0.5 M NaCl Solution - Sah, S. P.; Bhattarai, Jagadish (Journal of Nepal Chemical Society, 2009)
The corrosion behavior of the sputter-deposited amorphous or/and nanocrystalline W-Ni alloys is studied in neutral 0.5 M NaCl solution at 25ºC, open to air using immersion tests, electrochemical measurements and confocal scanning laser microscopic (CSLM) techniques. In general, the corrosion rates of the W-Ni alloys containing less than 20 at% nickel content are slightly lower than that of tungsten metal whereas the corrosion rates of the alloys containing 20 at% nickel or more increased with the addition of nickel in the alloys. The pitting corrosion is observed in the nickel-rich W-69Ni alloy from CSLM studies. The open circuit corrosion potentials of all the examined W-Ni alloys are shifted to noble direction with the addition of nickel content in the alloys. Keywords: W-Ni alloys, passivation, NaCl, electrochemical measurement, pitting. DOI: 10.3126/jncs.v23i0.2096 J. Nepal Chem. Soc., Vol. 23, 2008/2009 Page : 45-53